Fish scale hydroxyapatite/collagen composites incorporated with silver nanoparticles for bone filler applications - Jahil, Mustafa Mudhafar (Tanjong Malim, 2021)
Fish scale hydroxyapatite/collagen composites incorporated with silver nanoparticles for bone filler applications by Jahil, Mustafa Mudhafar